The Perception of Young Voters Towards the Integrity of the 2014 Election1 A Survey in Special Region of Yogyakarta - HAMDI, RIDHO AL; SURANTO, SURANTO; WIDODO, BAMBANG; SULAKSONO, TUNJUNG; DARUMURTI, AWANG (Jurnal Studi Pemerintahan, 2014)
The research examines the perception of youngvoters regarding the quality of theimplementation the 2014 election. There are sixindicators to measure the integrity: 1) theelection law, 2) the electoral procedure, 3) thevoter registration, 4) the political party and itscandidate registration, 5) the role of massmedia, and 5) the candidate campaign. Theresearch findings revealed that, in general,young voters have an adequate perceptionconcerning the electoral integrity. Morespecifically, the good perception is only to twothings namely political party and its candidateregistration and the electoral procedure. Therest is adequate perception. In addition, theresearch portrayed that young people havehighest trust merely to the CorruptionEradication Commision (KPK). On the otherhand, they have lowest trust into twoinstitutions: political party and parliament.Key words: Young voters, perception, the 2014election,Trust